2011
DOI: 10.1007/s00436-011-2298-3
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genes involving in tumorigenesis of cholangiocarcinoma induced by Opisthorchis viverrini infection

Abstract: Opisthorchiasis-associated cholangiocarcinoma (CCA) is one of main public health problems in Opisthorchis viverrini endemic areas. Although the definite relationship between prevalence of CCA and the parasite infection has been demonstrated, the molecular mechanism of tumorigenesis is still unknown. In the present study, by using animal model of opisthorchiasis-associated CCA, a kinetic analysis of cDNA microarray was performed to screen the candidate genes that involve in the development of opisthorchiasis-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 64 publications
4
18
0
Order By: Relevance
“…Several antioxidant genes including CAT showed downregulation in animal model of (Wu et al 2011). In agreement with other liver fluke, Fasciola hepatica, antioxidant potential was decreased in rat livers after post-infection (Kolodziejczyk et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several antioxidant genes including CAT showed downregulation in animal model of (Wu et al 2011). In agreement with other liver fluke, Fasciola hepatica, antioxidant potential was decreased in rat livers after post-infection (Kolodziejczyk et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous cDNA microarray analysis showed that some of S100 proteins were up‐regulated in the early stage of tumorigenesis in the animal model of O. viverrini infection‐induced CCA . S100 family is a super family of Ca2+‐binding proteins, consisting of >20 low molecular weight proteins which possess the EF‐hands to bind Ca2+.…”
mentioning
confidence: 99%
“…Furthermore, the results of our previous study showed that the decreased gene expression of CAT in the peripheral blood leukocytes of patients with opisthorchiasis is induced by Ov antigen (27). Additionally CAT was found to be downregulated in an animal model of opisthorchaiasis-associated CCA, detected via kinetic analysis using the cDNA microarray technique (28). …”
Section: Discussionmentioning
confidence: 99%